2006
DOI: 10.1007/s00221-005-0344-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rTMS over the left dorsolateral prefrontal cortex on Stroop task performance

Abstract: Several studies have demonstrated that repetitive transcranial magnetic stimulation (rTMS) can improve cognitive processing. Neuroimaging studies have shown the engagement of the left dorsolateral prefrontal cortex (DLPFC) in executive functioning, and more specifically during selective attention. In the present study, the influence of high-frequency rTMS over the left DLPFC on Stroop task performance in healthy female volunteers was investigated. As expected, reaction time on both the incongruent and congruen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 17 publications
12
85
3
Order By: Relevance
“…However, when evaluating the immediate effects of one single session of rTMS on this dysfunctional attentional processing, no instant improvements in inhibitory control were found, contrary to our expectations based on recent reports of enhanced top down attentional control (Vanderhasselt et al, 2006a(Vanderhasselt et al, , 2006b(Vanderhasselt et al, , 2007 and immediate changes in the inhibitory processing of negative information after prefrontal HF-rTMS in healthy volunteers (Leyman et al, in press). Yet, based on theoretical assumptions made by cognitive theories of depression (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, when evaluating the immediate effects of one single session of rTMS on this dysfunctional attentional processing, no instant improvements in inhibitory control were found, contrary to our expectations based on recent reports of enhanced top down attentional control (Vanderhasselt et al, 2006a(Vanderhasselt et al, , 2006b(Vanderhasselt et al, , 2007 and immediate changes in the inhibitory processing of negative information after prefrontal HF-rTMS in healthy volunteers (Leyman et al, in press). Yet, based on theoretical assumptions made by cognitive theories of depression (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Because recent studies within samples of healthy volunteers have demonstrated that one session of rTMS can induce changes in top-down attentional control (Vanderhasselt et al, 2006a(Vanderhasselt et al, , 2007 and in the inhibition of negative information (Leyman et al, in press), we hypothesized that rTMS would also result in immediate improvements in inhibitory control over negative information in a depressive patient sample. Because improvements in cognitive control in healthy volunteers were not accompanied by acute mood elevations, the latter might be a secondary-order effect only appearing after multiple treatment sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Unpublished data from left DLPFC (BA 9/46) stimulation using the same design revealed decreased RTs for color naming in both medium-and low-conflict conditions, whereas no effects were found after the word-reading instruction (Vanderhasselt, De Raedt, Leyman, & Baeken, 2009). These results are in line with the left, but not the right, DLPFC being related to a preparatory and temporary increased attentional set.…”
Section: Discussionmentioning
confidence: 90%
“…Since the Stroop interference effect remains a cornerstone on which the conflict-monitoring model is based, this review article focuses on lateralized processes of cognitive control based on different Stroop designs that have been used. Using a standard Stroop task with only a color-naming instruction and equal numbers of congruent and incongruent trials, one session of rTMS (10 Hz) over the left DLPFC (BA 9/46) had beneficial effects on both congruent and incongruent trials, whereas no changes occurred in the placebo sham condition (Vanderhasselt, De Raedt, Baeken, Leyman, & D'haenen, 2006). Although this can be considered to be consistent with the hypothesis that the left DLPFC plays a role in the implementation of control, by representing and actively maintaining the attentional demands of the task (i.e., imposing an attentional set: Harrison et al, 2005), one could also argue that enhanced attentional control should lead to a decreased interference effect (MacDonald et al, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…rTMS has also been applied offline to pre-treat a given cortical area to create a 'virtual lesion' that outlasts the duration of the stimulation (Walsh and Cowey, 2000), providing considerable advantages as compared with online stimulation (Robertson et al, 2003). Offline high-frequency rTMS over the left DLPFC has been shown to disrupt performance on the Stroop task (Vanderhasselt et al, 2006b), task-set switching (Vanderhasselt et al, 2006a), and divided attention tasks (Wagner et al, 2006). Recently, Ko et al (2008b) applied rTMS (stimulation train consisted of five pulses of 20 Hz rTMS; the stimulation intensity was set to 110% of resting motor threshold of FDI and the total stimulation time was 36 min) to the mid-DLPFC region to test the hypothesis that such stimulation affects monitoring of information in working memory without interfering with other executive functions.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%